How Green Self Image Affects Subjective Well-Being: Pro-Environmental Values as a Social Norm - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2017)
Recent literature has found that individuals holding a greener self-image display higher levels of life satisfaction. We extend the single-country setting of that research to a transnational perspective and explore whether a relationship exists between green self-image (GSI) and life satisfaction (LS), both European-wide and at the national level. In order to explain differences in the GSI-LS relationship across nations and time, we study the role of pro-environmental values as a shared social norm. We find a significantly positive GSI-LS relationship in a pool of 35 European countries and in the majority of individual countries. In addition, we show that the well-being benefit of holding a green self-image is greater in societies that are less divided with respect to environmental attitudes, that is, where being green is a shared social norm.
Keywords: I31; Q50; Z13; 330; green self-image; subjective well-being; life satisfaction; social norm; social division